MRI of CNS lymphoma with choroid plexus involvement in five dogs and one cat. (26th March 2021) - Lampe, R.; Levitin, H. A.; Hecht, S.; Vieson, M. D.; Selting, K. A.; Hague, D. W.; Foss, K. D.
Abstract : Objectives: To describe the clinical features, magnetic resonance imaging (MRI) findings, and outcome of dogs and cats with central nervous system (CNS) lymphoma that involved the choroid plexus. Materials and Methods: A bi‐institutional retrospective study of MRI of dogs and cats with CNS lymphoma, in which the choroid plexus was affected on MRI. Signalment, clinical, MRI, clinicopathologic and histopathologic findings were recorded and evaluated. Results: CNS lymphoma with choroid plexus involvement on the MRI was identified in five dogs and one cat. MRI revealed diffuse enlargement and multifocal nodularity in the choroid plexus in most cases, with the fourth ventricle the most common site affected. Five of the cases had signs of extraneural involvement (including the cat), while the sixth case was not staged. Four of five CSF samples analysed provided a diagnosis of lymphoma. Clinical Significance: We report MRI findings of CNS lymphoma involving the choroid plexus. These results show the importance of recognising novel imaging patterns and the potential utility of CSF collection in diagnosing CNS lymphoma involving the choroid plexus ante mortem.